Autologous erythrocytes delivery of berberine hydrochloride with long-acting effect for hypolipidemia treatment. (1st January 2020) - Cheng, Zhongyao; Liu, Siyu; Wu, Xinyi; Raza, Faisal; Li, Yichen; Yuan, Weien; Qiu, Mingfeng; Su, Jing
Abstract: Discovery of novel pharmacological effects of berberine hydrochloride (BH) has made its clinical application valuable. However, further development and applications of BH are hampered by its short half-life and the side effects associated with its intravenous (iv) injection. To improve the hypolipidemia efficacy and reduce side effects, we encapsulated BH into biocompatible red blood cells (RBCs) to explore its sustained-release effect by hypotonic pre-swelling method. From in vitro evaluation, BH loaded RBCs (BH-RBCs) presented similar morphology and osmotic fragility to native RBCs (NRBCs). After the loading process, the BH-RBCs maintained around 69% of Na + /K + -ATPase activity of NRBCs and phosphatidylserine externalization value of BH-RBCs was about 26.1 ± 2.9%. The survival test showed that the loaded cells could circulate in plasma for over 9 d. For in vivo evaluation, a series of tests including pharmacokinetics study and hypolipidemic effect were carried out to examine the long-acting effect of BH-RBCs. The results showed that the release of BH in the loaded cells could last for about 5 d and the hypolipidemic effect can still be observed on 5 d after injection. BH-loaded autologous erythrocytes seem to be a promising sustained releasing delivery system with long hypolipidemic effect.